2013
DOI: 10.1103/physrevb.88.075139
|View full text |Cite
|
Sign up to set email alerts
|

Disordered conduction in single-crystalline dimer Mott compounds

Abstract: We study the temperature and frequency dependence of the dielectric constant and the ac conductivity in the dimer Mott insulator family β-type Pd(dmit) 2 (where dmit denotes 1,3-dithiole-2-thione-4,5-dithiolate). We find that all compounds within this family have relaxorlike dielectric relaxation with a Curie-Weiss increase in the dielectric constant with decreasing temperature. An analysis of the dielectric data shows a clear relation between electronic correlation and the dipole-dipole interaction; also, geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
(50 reference statements)
2
20
1
Order By: Relevance
“…These experimental results indicate that the inhomogeneity of the dimerization increases from the AF to the SL states. This conclusion is inconsistent with that of a previous report, in which the dielectric constant was found to have no obvious relationship with T AF 52 . This inconsistency suggests that the anomaly in the dielectric constant should include not only the inhomogeneity due to the bond alternations but also macroscopic inhomogeneities.…”
Section: Discussioncontrasting
confidence: 99%
“…These experimental results indicate that the inhomogeneity of the dimerization increases from the AF to the SL states. This conclusion is inconsistent with that of a previous report, in which the dielectric constant was found to have no obvious relationship with T AF 52 . This inconsistency suggests that the anomaly in the dielectric constant should include not only the inhomogeneity due to the bond alternations but also macroscopic inhomogeneities.…”
Section: Discussioncontrasting
confidence: 99%
“…For β ′ -EtMe 3 Sb[Pd(dmit) 2 ] 2 , a similar enhanced dielectric constant was reported in Ref. 13. Although the enhancement of the dielectric response shows the slow charge dynamics of the sample, it is still under debate whether the magnetically active [Pd(dmit) 2 ] 2 dimers or the cations that is electronically closed cause the slow fluctuation of the electrons.…”
Section: Resultssupporting
confidence: 79%
“…It was previously found that the ac responses of the dielectric constants of the molecular-based QSLs β ′ -EtMe 3 Sb[Pd(dmit) 2 ] 2 and κ-(BEDT-TTF) 2 Cu 2 (CN) 3 show similar anomalies. 12,13 The dielectric constants ǫ ′ of both materials show enhancement between 10 K and 50 K at low frequencies below 1 MHz. The resemblance of the dielectric response for very different counter ions composed of different elements (EtMe 3 Sb and Cu 2 (CN) 3 , both are electronically closed) indicates that the lowenergy dielectric fluctuations originate from dimerized molecules that hold S = 1/2 spins.…”
Section: Introductionmentioning
confidence: 99%
“…As regards organic salts, strong coupling between the spin and electric polarization at each spin site and its importance to the liquid-like behavior have been noted 14,15 . In the low-temperature region, a random freezing of the electiric polarization is indicated by the glassy response in the dielectri properties 16,17 . Accordingly, the spin-density distribution at each lattice site should be also randomly freezing and causes the bond-randomness.…”
Section: Introductionmentioning
confidence: 99%